Administração e gestão social : aspectos dimensionais do desenvolvimento sustentável em municípios sergipanos - Bitencourt, Daniela Venceslau (2015)
Efforts made by the public, private and third sector to local sustainable development has been, as a general rule, concentrated in index of development and growing interest in the use of indicators as a way to cater to local interests, decreased poverty and meeting the basic needs of their citizen. City managers need to broaden the debate about the responsibilities of citizens in participatory decision-making process in order to promote social well-being and sustainable local development. In this respect, the present thesis aims to analyze the role of social management as a promoter of sustainable local development and, to that end, sought to calculate the indexes of sustainable development of municipalities in the State of Sergipe; assessing sustainability levels between dimensions (demographic, economic, social, institutional and political, cultural and environmental) of each municipality; present an overview of the situation of the levels of sustainability among the municipalities in the State of Sergipe; as well as explain the social management in the promotion of sustainable local development.For the implementation of this research trajectory became the option for both, the dialetic and the comparative method, within the data obtained through the calculation of indixes of sustainable development among municipalities, their bottlenecks points between the dimensions through the intersection of variables extracted from the information found: in the IBGE; the SNIS; the DATASUS; the FEINBRA; and other public domain sites on the situation of each municipality. It is concluded that the participation of the citizens should be considered as a sine qua nom condition in decision-making and in obtaining sustainable local development and presents itself as a challenge for managers working in the perspective of social management as a addition to their administrative skills, developing multidimensional actions involving resources, culture, generations, income and employment, education, public health prevention; organized community, interinstitutional collaboration, public-private partnerships of collective mode and with social responsibility.